2012
DOI: 10.1088/0029-5515/52/3/037001
|View full text |Cite
|
Sign up to set email alerts
|

Conference Report on the 2nd International Symposium on Lithium Applications for Fusion Devices

Abstract: The 2nd International Symposium on Lithium Applications for Fusion Devices (ISLA-2011) was held on 27–29 April 2011 at the Princeton Plasma Physics Laboratory (PPPL) with broad participation from the community working on aspects of lithium research for fusion energy development. This community is expanding rapidly in many areas including experiments in magnetic confinement devices and a variety of lithium test stands, theory and modeling and developing innovative approaches. Overall, 53 presentations were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 2 publications
0
38
0
Order By: Relevance
“…Lithium conditioning of plasma-facing components has improved plasma performance and reduced recycling on multiple fusion devices [1]. The chemical composition of the lithium surface, which is affected by exposure to ambient air during venting and residual vacuum gases during operation, strongly influences interactions at the plasma-surface interface.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium conditioning of plasma-facing components has improved plasma performance and reduced recycling on multiple fusion devices [1]. The chemical composition of the lithium surface, which is affected by exposure to ambient air during venting and residual vacuum gases during operation, strongly influences interactions at the plasma-surface interface.…”
Section: Introductionmentioning
confidence: 99%
“…These results have therefore confirmed the effectiveness of lithium PFC coatings in multiple devices and magnetic confinement configurations. Summary articles of the more recent lithium experiments and related research can be found in the conference reports for the 1 st and 2 nd workshops on lithium applications in fusion plasmas [20,21]. In addition to the plasma performance improvement, which was the main motivation for the earlier experiments, the recent lithium research has been also trying to address the reactor divertor PFC issues as noted by the APEX study.…”
Section: Lithium Experiments In Present Day Fusion Devices (2000mentioning
confidence: 99%
“…The lightest alkali metal lithium considered as a "future and strategic metal" is widely used in the fields of porcelain and glass making, refrigeration, metallurgy, medicine, aerospace, military industry, atomic energy, alloys and batteries, among others [1][2][3][4][5][6][7] . Lithium resources exist naturally either in solid ores or in liquid brines.…”
Section: Introductionmentioning
confidence: 99%